Capacity vs. Performance: Maximizing a Patient's Carryover From Physical Therapy to Community Life - Wadsworth, Brian (Archives of physical medicine and rehabilitation, 2021)
Assess PT's impact on a patient's community performance with and without attention to objective self-monitoring. Case study, within subject comparison. Outpatient PT. A 62-year-old male 1.5yrs post-stroke. No contraindications to high intensity gait training (HIGT). Treatment involved HIGT for 30minutes/session over 20 sessions. During the initial 10 visits the patient was encouraged to walk a minimum of 30minutes/day. For the second 10 visits the patient was instructed to: walk a minimum of 10,000 steps per day (SPD) and check his step totals daily. PT also reviewed the patient's steps each session. SPD; 10-Meter Walk Test (10MWT); 6-Minute Walk Test (6MWT); Functional Gait Assessment (FGA). By his 10th visit the patient's functional capacity objectively improved in a clinically meaningful way: 10MWT 1.05m/s to 1.50m/s; 6MWT 432m to 530m; and FGA 17/30 to 24/30. Patient consistently achieved HIGT target HR range (average session intensity 83% HRmax). Patient's community performance increased from 7,033 SPD (initial evaluation) to 7,781 SPD (10th visit). Following the above education his average SPD increased to 29,843. This case study supports direct patient education and objective daily step monitoring to promote improved patient performance. This patient demonstrated minimal change in his daily functional performance, despite clinically significant changes to his capacity, without this education. Greater emphasis on self-monitoring appeared to positively influence the patient's average SPD between his 10th and 20th visit (Δ 22,062 SPD). In conclusion, it should not be assumed that improvements in capacity correlate automatically with increased performance outside of the clinical setting. Objectively tracking performance, and problem solving with the patient to overcome any self-perceived barriers, may help bridge the gap between the clinic and community to maximize quality of life. Nothing to disclose.